Characterization and toxicology evaluation of low molecular weight chitosan on zebrafish. (15th July 2020) - Chou, Chih-Ming; Mi, Fwu-Long; Horng, Jiun-Lin; Lin, Li-Yih; Tsai, Min-Lang; Liu, Chao-Lin; Lu, Kun-Ying; Chu, Cheng-Ying; Chen, Yu-Tzu; Lee, Yu-Lin A.; Cheng, Chia-Hsiung
Highlights: LMWCS damages cell membrane of ZFL cells reducing cell viability. LMWCS damages yolk of zebrafish larvae and gill filaments of adult zebrafish inducing death. Purification and neutralization with Na2 HPO4 could eliminate toxicity of LMWCS nanoparticle. Abstract: Chitosan is suggested as no or low toxicity and biocompatible biomaterial. Digestion of chitosan to reduce molecular weight and formulate nanoparticle was generally used to improve efficiency for DNA or protein delivery. However, the toxicity of low-molecular-weight chitosan (LMWCS) towards freshwater fishes has not been well evaluated. Here, we reported the toxic mechanism of LMWCS using zebrafish ( Danio rerio ) liver (ZFL) cell line, zebrafish larvae, and adult fish. LMWCS rapidly induced cytotoxicity of ZFL cells and death of zebrafish. Cell membrane damaged by LMWCS reduced cell viability. Damaged membrane of epithelial cell in zebrafish larvae induced breakage of the yolk. Adult fish exhibited hypoxia before death due to multiple damages induced by LMWCS. Although the toxicity of LMWCS was revealed in zebrafish model, the toxicity was only present in pH < 7 and easy be neutralized by other negative ions. Collectively, these data improved a new understanding of LMWCS properties.